Analisis Regresi Logistik Multinomial untuk Menentukan Faktor-Faktor yang Mempengaruhi Jenis Penyakit pada Mahasiswa (Studi Kasus: Mahasiswa Program Studi Statistika, Jurusan Matematika, Universitas Negeri Gorontalo) - Nathania Oktavia Gunawan; Salmun K. Nasib (Transbahasa, 2025)
Final-year students often experience illnesses due to numerous challenges, such as repeated revisions, difficulty finding references, and time constraints in completing their final assignments. Various factors contribute to the occurrence of illnesses among students. Multinomial logistic regression analysis is used to identify which factors significantly influence the types of illnesses in students. The data source used in this research was primary data, with a sample consisting of 83 active Statistics students at Universitas Negeri Gorontalo who met the inclusion criteria. The dependent variable was the type of illness, while the independent variables included age, gender, eating habits, sleeping patterns, and stress levels. The research instruments were validated using Pearson correlation analysis and tested for reliability using Cronbach's alpha statistical test. The results of the chi-square correlation test indicated that the stress level variable had a significant relationship (p-value = 0.03853) with the dependent variable. Based on the results of the multinomial logistic regression analysis, it was found that there is a 10.85% relationship between the stress level variable and the types of illnesses in students.